Decentralized proportional-integral sliding mode tracking control for A class of nonlinear interconnected uncertain system - Ahmad, Mohamad Noh; Osman, Johari H. S.; A. Ghani, Mohd. Ruddin (Penerbit UTM Press, 2001)
A decentralized sliding mode controller for a class of nonlinear interconnected uncertain systems is presented in this paper. It is assumed that the plant to be controlled is represented by interconnected sub-systems and the local dynamics of each sub-system is represented by its nominal and bounded parametric uncertainties. It is also assumed that the interconnection dynamics is also represented in the same manner and it is further assumed that the matching conditions hold for every sub-system. A robust decentralized sliding mode controller is derived such that for each sub-system, the actual trajectory tracks the desired trajectory using only the local states information. The Proportional-Integral sliding mode is chosen to ensure the stability of the overall dynamics during the entire period i.e. the reaching phase and the sliding phase. Mathematical proof of the proposed controller is presented and the results are verified using a case study.